Serum and Tissue Periostin Expression in Rhinosinusitis With Nasal Polyps - Danielides, Gerasimos; Lygeros, Spyridon; Kyriakopoulos, Georgios; Tsapardoni, Foteini; Grafanaki, Katerina; Stathopoulos, Constantinos; Naxakis, Stephanos; Danielides, Vassileios (American journal of rhinology & allergy, 2025)
BackgroundThere is increasing evidence of the contribution of periostin in the pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP).ObjectiveThis study aims to investigate the expression of periostin in nasal polyp tissue along with serum periostin and its potential function as a biomarker.MethodsThe study included 36 CRSwNP patients and 12 controls. Nasal polyp tissue from CRSwNP patients and inferior turbinate mucosa samples from controls were intraoperatively collected. gene mRNA expression from nasal polyp tissue was assessed with polymerase chain reaction and periostin levels on tissue samples were measured with ELISA and Western Blot. ELISA was performed to evaluate serum periostin on blood samples collected from patients undergoing functional endoscopic sinus surgery for CRSwNP ( = 36) and results were compared with assays performed on control subjects ( = 12).ResultsTissue periostin gene expression in terms of mRNA levels was significantly elevated in patients with CRSwNP than in healthy control subjects ( -value <.05). Τissue periostin values in CRSwNP patients were also significantly higher in CRSwNP compared to controls. A positive correlation between periostin levels and the presence of asthma and smoking was observed in the patient group. Serum periostin did not present a statistically significant difference between the 2 groups.ConclusionsOur data suggest that periostin expression is upregulated in nasal polyps and might determine a crucial role in the occurrence and evolution of the disease. Periostin appears to be a promising therapeutic target candidate in CRSwNP.